LITERATURE REVIEW: SEXUAL DYSFUNCTION IN PATIENTS WITH SCHIZOPHRENIA - Sitti Rahma Soleman; Warih Andan Puspitosari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Schizophrenia is a serious mental disorder characterized by incoherent thoughts, delusions, hallucinations, and impaired concentration. Antipsychotic therapy in schizophrenic patients is reported to be the main factor causing sexual function problems in schizophrenic patients. As humans who have biological needs, the function of sexuality in people with schizophrenia must be considered. The assessment of the function of sexuality often experiences difficulties because it is still considered taboo and neglected. The aim of the study was to review research on the factors that influence sexual functioning in schizophrenic patients. a literature review study approach was used to reviewed several research on sexuality in schizophrenia patients. Article search through EBSCO, Proquest, Science Direct, Pubmed, and Google Scholar. Search results, founds that 398 articles, then analyzed so that 19 relevant studies were obtained. The key words used were schizophrenia, sexuality, sexual function, sexual dysfunction. From 19 literature found that there are several factors that cause sexuality problems in schizophrenia patients. These factors are the use of antipsychotics, stigma, discrimination, culture, beliefs, and spirituality. Untreated sexual dysfunction can have negative effects such as lowering self-esteem, worsening social isolation, and the ability to build sexual relationships with partners. In addition, sexual dysfunction can also affect the quality of the marriage, which can lead to permanent disputes and even divorce. Other effects of sexual dysfunction can affect quality of life, low self-esteem, patient mood, medication adherence, and adherence to therapy. The use of antipsychotics is still the biggest cause of sexual dysfunction in schizophrenic patients. Untreated, sexual dysfunction will affect patient's quality of life. Therefore, it is hoped that the professional team in this case doctors and nurses can improve the care and evaluation of sexual dysfunction related events in schizophrenia patients.